Excellence, Innovation and Academic Freedom in University Policy in Iceland - Ingólfur Ásgeir Jóhannesson 1954- (2013)
Fræðigrein This article analyzes three reports on higher education, research and innovation policy in Iceland by using a Foucauldian discourse analysis approach. The reports were released in 2009 and 2012, emphasizing the simplification of the research and innovation system in Iceland. While on the surface the reports include practical recommendations, the study reveals a strong moral stance in the reports which express concerns that too many universities and two small institutions spread efforts too widely. Suggestions to reorganize the system tend to be presented by simply stating that it is important to do so, but sometimes such assertions are also interwoven with arguments for larger and more powerful universities and research institutions. There is a focus in the reports on innovation and the creation of economic value. Research, science, and innovation are firmly combined with the goal of economic growth. There is the undertone that it is relatively easy to define what is good research or even quality research; and the chief criterion seems to be that good research is research that is useful for business and industry. Academic freedom, on the other hand, is rarely discussed in the reports.